Albert, Prince Consort of Victoria, Queen of Great Britain, correspondence - Albert, Prince Consort, consort of Victoria, Queen of Great Britain, 1819-1861.
Two photocopies of letter (Buckingham Palace; 1853 April 8) from Albert to Frederick William Louis, later William I, German emperor, regarding the christening of Prince Leopold on June 28, 1853. ALS (British Museum; 1935 April 12) from H. R. Aldridge to Ray Baker Harris concerning Albert's letter. Includes two typewritten transcripts of Albert's letter and a typewritten transcript of Aldridge's letter.
Negative photocopies and typewritten transcripts.
Royal consort of Queen Victoria.
Collection material in German, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Aldridge, H. R. -- Correspondence; Harris, Ray Baker, -- 1907- -- Correspondence; Leopold, -- Prince, Duke of Albany, -- 1853-1884.; William -- I, -- German Emperor, -- 1797-1888 -- Correspondence; Royal consorts -- Great Britain